Marketing Strategy For Matahari.Com Customers In Medan: A Study Of Online Fashion Product - Sugito, Sugito (SEAN Institute, 2024)
The objective of this research is to investigate the online marketing strategies for fashion products to customers of Matahari.com in Medan. The research was conducted using a qualitative descriptive approach and data was collected through observation, interviews, and documentation techniques. The research findings indicate that online marketing methods utilize electronic media and internet network access. Currently, online product marketing predominantly employs smartphones, as many consumers prefer the convenience of shopping from home rather than braving the heat outside. To effectively market fashion products on Matahari.com, a strategy must consider the four Ps: product, place, distribution, and price.